SHEARS INC. Salon Management System - Annie Chai; Chuah Chai Wen (Politeknik Negeri Padang, 2017)
Management system is the framework of processes and procedures used to ensure that an organization can fulfil all task required to achieve its objectives. In recent times, most organization will opt to use management system in their daily business task. There are those who still use the non-computerized system as opposed to the computerized management system. The non-computerized system may be effective but it also causes greater task load when implemented. Computerized system makes it easier for users with functions such as searching, automatic calculation, and display of related information with minimal queries. The development of Shears Inc. Salon Management System is to act an alternative to the non-computerized system implemented by Shears Inc. Salon. The system developed will be able to decrease the task load of owner and employees of Shears Inc. Salon. Software Development Life Cycle methodology is used in the development of Shears Inc. Salon Management System. This system is installed in computer device. It runs on local host server and MySQL is used as the database server. The programming language used in developing Shears Inc. Salon Management System is PHP programming language. Hence, Shears Inc. Salon Management System is an alternative for the salon to manage recording tasks.